2003
DOI: 10.1063/1.1580097
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of oxygen bonding on diamond surfaces by low energy electron stimulated desorption and high resolution electron energy loss spectroscopy

Abstract: Articles you may be interested inTwo bonding configurations of acetylene on Si ( 001 ) -( 2 × 1 ) : A combined high-resolution electron energy loss spectroscopy and density functional theory study Mechanism of low-energy electron stimulated desorption of O − from hydrogenated and hydrogen-free diamond surfaces exposed to activated oxygen In this work we correlate between O Ϫ electron stimulated desorption ͑ESD͒ from hydrogenated and bare polycrystalline diamond films exposed to thermally activated oxygen for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This band can be assigned to uCH x deformation vibrations, both saturated and unsaturated, [18][19][20] and stretching vibrations of the C v C dimers. [23][24][25] However, based on a comparison between HREELS peaks and characteristic absorption bands observed by IR spectroscopy, it may be suggested that the 125 meV energy loss is due to peroxide-type vibrations ͑C u O u O u C͒ and the 135 meV peak is most likely due to ether, C u O u C type bonds. 17,18 The spectrum also displays multiple peaks in the 100-135 meV range, which are difficult to assign unambiguously.…”
Section: Resultsmentioning
confidence: 99%
“…This band can be assigned to uCH x deformation vibrations, both saturated and unsaturated, [18][19][20] and stretching vibrations of the C v C dimers. [23][24][25] However, based on a comparison between HREELS peaks and characteristic absorption bands observed by IR spectroscopy, it may be suggested that the 125 meV energy loss is due to peroxide-type vibrations ͑C u O u O u C͒ and the 135 meV peak is most likely due to ether, C u O u C type bonds. 17,18 The spectrum also displays multiple peaks in the 100-135 meV range, which are difficult to assign unambiguously.…”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53][54]57,58,[62][63][64][65][66][67] In order to clarify the origin of the peaks at 300, 450, and 600 meV, an ion irradiation experiment was performed on a well-defined diamond surface. [74,75] Ion irradiation results in partial amorphization of the film surface, so the change in the shape of the spectrum following the ion irradiation may be associated with the change of the surface crystalline structure.…”
Section: Hreels Mode Positionmentioning
confidence: 99%
“…[2][3][4][5][10][11][12][13] Spectroscopic methods such as infrared ͑IR͒ spectroscopy is a useful noninvasive method to characterize the surface structures. The developed surface of diamond particles can contain a large number of surface inorganic groups such as ether ͑-C-O-C͒, peroxide ͑-C-O-O-͒, carbonyl ͑-C v O͒, and hydroxyl-type ͑-C-O-H͒ bonding, as well as hydrocarbon fragments.…”
Section: Introductionmentioning
confidence: 99%